The Implementation of Project-Based Learning to Enhance Collaborative Skills in Senior High School - Khasanah, Laila Nur; Maksum, Muh. Nur Rochim; Zahid, Nurul Nashuha Binti (Universitas Muhammadiyah Surakarta, 2025)
Collaboration skills are an important competency in facing the challenges of the 21st-century world. Therefore, collaboration skills need to be developed since students are in school. The Project-Based Learning (PJBL) learning model, whose learning center is focused on students, is said to be able to improve students' collaboration skills. This study aims to describe the implementation of the PjBL model in Senior High School (SMA) and examine its contribution to improving students' collaboration skills. This study uses a literature review method. Analysis was carried out on the implementation of PjBL and the indicators of collaboration skills developed. The data was taken from the Google Scholar and Publish or Perish databases, with the article criteria being an Indonesian article about implementing the Project-Based Learning learning model in high school students with a publication period of 2015 to 2025. 18 articles met these criteria. The results of the study show that to obtain effective implementation of PjBL, teachers must know the proper stages of implementation of PjBL and be able to carry out their role as facilitators well. PjBL has improved students' collaboration skills in five key dimensions: active participation, effective communication, group responsibility, respect for differences, and resource management. These findings reinforce the importance of implementing PjBL as an effective approach in shaping students' collaboration skills in the 21st-century learning era.